2013
DOI: 10.3855/jidc.2981
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of post-caesarean surgical site infections in a hospital with limited resources, Cambodia

Abstract: Introduction: In Cambodia, we implemented a pilot surveillance of superficial surgical site infections (SSSI) following caesarean deliveries (CD) in a provincial hospital, to estimate their incidence, describe their clinical management, and determine their causative pathogens. Methodology: Between October 2010 and February 2011, all women admitted for CD were included in the surveillance. Their clinical condition was monitored for a post-operative period of 30 days, including two assessments performed by surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 28 publications
2
23
0
1
Order By: Relevance
“…A study in Nigeria [5] found that in 25% of cases of surgical site infection, the operative indication was fetopelvic disproportion compared with 15.3% in control cases. In Cambodia, patients with fetopelvic disproportion were 3.5 times more likely to present a surgical site infection after cesarean delivery [14].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Nigeria [5] found that in 25% of cases of surgical site infection, the operative indication was fetopelvic disproportion compared with 15.3% in control cases. In Cambodia, patients with fetopelvic disproportion were 3.5 times more likely to present a surgical site infection after cesarean delivery [14].…”
Section: Discussionmentioning
confidence: 99%
“…19 In Cambodia, estimates range from 14% to 30%. 4,19,20 Of 21 countries surveyed in 2010-2011, Cambodia had the largest increase in c-section rate (+ 16.8% per year between 2007-2008 and 2010-2011). 19 Comparisons of successive Cambodian Demographic and Health Surveys (CDHS) also suggest a sharp increase from 0.8% to 6.3% in the country, and from 4.6% to 14.4% in Phnom Penh between 2000 and 2014.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 They lead to more hospital-acquired site infections, and delays in breastfeeding. 4,5 C-section can also compromise future pregnancies, and have long term negative effects for the newborns, such as obesity, asthma, type-1 diabetes, and lead to unexplained stillbirths in the second pregnancy. 2,[6][7][8][9][10][11][12] These risks explain why c-section on demand is considered, "an expensive and dangerous luxury".…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In many institutions, the antibiotic administration is performed after the umbilical cord has been clamped, justified by the neonatal impact of antimicrobial use. 4,5 Although antimicrobial prophylaxis reduces the risk of endometritis and incisional SSI when administered correctly, much has been discussed about its real impact due to the small number of studies and their limitations. 4,6,7 The rates of SSI after CS reported in the literature ranges from 3% to 15%, depending on the surveillance methods used to identify infections, the patient population, and the use of antibiotic prophylaxis.…”
Section: Introductionmentioning
confidence: 99%